Tradisi dan Reformasi Pesantren: Kurikulum dan Kewibawaan Kyai dalam Pemikiran Zamakhsyari Dhofier dan Nurcholish Madjid - Ali Masdar Fahim; Muhammad Husni (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This paper analyzes the implications of the ideas of Zamaksyari Dhofier and Nurcholish Madjid on reforming pesantren education in Indonesian society. To this end, a critical document analysis is conducted using a qualitative approach, evaluating the ideas presented in Tradisi Pesantren and Bilik-bilik Pesantren, supplemented by secondary literature on pesantren modernization. From the findings, it is apparent that the ideas of the reform-minded thinkers present a comprehensive framework for the five main aspects of pesantren (dormitory, mosque, classical texts, students, and kyai leader); the learning of classical texts through "sorogan and bandongan disciplines"; and that the kyai is a quasi-absolute authority, molding the community's moral and social orientation. On the contrary, the ideas of the modernizers center on the futility of the explicitly formulated educational aims and goals; the limitation and weaknesses of the dualistic notions on the religious and "general" sciences; and the need for fundamental reforms in pesantren education in the curriculum, method, organizational, and socio-economic terms. The integration of the ideas on a conceptual framework presents a leadership and curriculum construct that is socially adaptive. This paper offers a new insight into the area of Islamic education as it attempts to reconcile the romance of tradition, as described by Zamakhshari's ideas, with the reformist ideas of Nurcholish.   Keywords: Curriculum, Kyai, Pesantren